Standard specification for seamless medium-carbon steel boiler and superheater tubes. (American Society for Testing and Material, 2008)
This specification2 covers minimum-wall-thickness, seamless medium-carbon steel, boiler tubes and boiler flues, including safe ends (see Note 1), arch and stay tubes, and superheater tubes.